Rare case report: a case of histological type transformation of lung cancer caused by neoadjuvant immunotherapy - Li, Quanqing; Zhang, Guangxin; Yang, Hao; Li, Jindong (Frontiers in Oncology, 2024)
Lung cancer remains the leading cause of cancer-related mortality, with 1.8 million deaths per year. Small cell lung cancer and non-small cell lung cancer (NSCLC) are the main cancer types. Approximately 85% of cases are NSCLC, including adenocarcinoma, s quamous cell carcinoma, and large cell carcinoma. In this reported treatment case, the tumor histological type changed after targeted therapy, which has not been previously well documented. The patient was a 67-year-old woman diagnosed with squamous cell carcinoma via bronchoscopy. She received five neoadjuvant immune monotherapies. The lesion shrank, but then progressed, with a diagnosis of small cell carcinoma via bronchoscopy. This finding suggests that tumor acquisition of resistance as manifested by cancer type changes need consideration and study in the application of this particular type of immunotherapy.